Enhancing Porous Concrete Strength Through Superplasticiser Addition - Seng Hansen; BMAS Anaconda Bangkara; Amalia Fathimah Azh Zhahra Mughni; Ario Bintang Koesalamwardi; Aldi Kurnia (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2026)
Porous concrete is widely used as a sustainable construction material since it allows water to pass through its structure, reducing surface runoff and supporting groundwater recharge. However, its application is often limited by its low compressive strength. This study investigates the effect of adding superplasticiser at varying dosage levels: 0.3%, 0.6%, and 0.8% of cement weight, on the mechanical properties of porous concrete. The research was conducted through laboratory experiments, with material testing, slump testing, and compressive strength testing at 7 and 28 days of curing. The results showed that the addition of superplasticiser significantly improved the compressive strength of porous concrete without affecting its porosity. The highest compressive strength was achieved at a 0.8% dosage, reaching 23.01 MPa at 28 days, which represents a 21.4% increase compared to normal porous concrete. The slump test confirmed that all concrete mixtures maintained near-zero slump values, ensuring that permeability was not compromised. These findings suggest that superplasticiser is an effective additive for improving the strength of porous concrete while preserving its essential drainage function. The research supports the broader application of porous concrete in sustainable infrastructure, especially in areas where both strength and water management are critical.